Warehouse-based, immunopeptidome-guided design of personalised peptide vaccines shows feasibility in clinical trial evaluation in CLL patients - Heitmann, Jonas S.; Jung, Susanne; Wacker, Marcel; Maringer, Yacine; Nelde, Annika; Bauer, Jens; Denk, Monika; Hoenisch-Gravel, Naomi; Richter, Marion; Oezbek, Melek T.; Dubbelaar, Marissa L.; Bilich, Tatjana; et al. (Frontiers in Immunology, 2024)
Cancer peptide vaccination represents a promising therapeutic approach, but has been hampered by lack of suitable antigens and restricted applicability due to different HLA backgrounds of individual patients. We here introduce a novel warehouse-based concept for composition of personalized peptide vaccines and report on its successful application in a Phase II clinical trial in patients with chronic lymphocytic leukemia (CLL) after first-line therapy. 26 CLL patients in at least partial remission (PR) after 6 months of immuno-chemotherapy were vaccinated with a personalized vaccine compiled from a premanufactured peptide warehouse comprising immunopeptidome-defined CLL-associated peptides. Primary objective was evaluation of immunogenicity, secondary objectives were safety and minimal residual disease (MRD) response. Immunopeptidome-guided vaccine composition was throughout successful, proving the feasibility of warehouse-based vaccine design. Vaccination was well tolerated, with local injection site reactions being the most common adverse event. Only few patients showed vaccine-induced T cell responses, attributable to their inability to mount strong immune responses due to immune-chemotherapy and lack of potent adjuvant formulations. Both issues are addressed within a follow-up trial (NCT04688385), combining the immunopeptidome-guided warehouse-based vaccine design reported here with a potent novel adjuvant evaluating personalized multi- peptide vaccination in CLL patients under T cell supportive BTK inhibitor therapies.Clinical trial registrationwww.clinicaltrialsregister.eu, identifier NCT02802943.